*This preview shows
page 1. Sign up
to
view the full content.*

**Unformatted text preview: **15.62: (a) (b) The wave moves in the + x direction with speed v, so in the expression for y (x,0) replace x with x - vt : for ( x - vt ) < - L 0 h ( L + x - vt ) L for - L < ( x - vt ) < 0 y ( x, t ) = h ( L - x + vt ) L for 0 < ( x - vt ) < L 0 for ( x - vt ) > L (c) From Eq. (15.21): for ( x - vt ) < - L - F (0)(0) = 0 2 y ( x, t ) y ( x, t ) - F (h L)(- hv L) = Fv(h L) for - L < ( x - vt ) < 0 P ( x, t ) = - F = 2 x t - F (- h L)(hv L) = Fv(h L) for 0 < ( x - vt ) < L - F (0)(0) = 0 for ( x - vt ) > L Thus the instantaneous power is zero except for - L < ( x - vt ) < L, where it has the constant value Fv(h L) 2 . ...

View
Full
Document